2016
DOI: 10.1016/j.foodchem.2015.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of anthocyanins and polyphenols from black rice (Oryza sativa L.) by modeling and assessing their reversibility and stability

Abstract: This study was aimed the extraction of total flavonoids, anthocyanins and phenolics, as well as the antioxidant activity of black rice (Oryza sativa) and to study the stability in relation to pH, light and copigmentation. Variations in temperature (10-50°C), time (20-80min), and solid-solvent ratio (1:15-1:45) were studied using a Box-Behnken design. The regression models were significant (P<0.001) and determination coefficients ⩾0.900. Extraction at 34.7°C for 80min using a solid:solvent ratio of 1:30 rendere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
93
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(114 citation statements)
references
References 47 publications
(66 reference statements)
13
93
2
6
Order By: Relevance
“…It was reported previously in pomegranate juices; the diglucoside AC was more stable than the monoglucosides. 8 This was parallel with present study and Dionex; 9 Cy3, 5 and Pg3, 5 compositions are higher than Cy3 and Pg3. However, this was contrary to Miguel et al 6 in which there was a high decrease of Cy3, 5 than Cy3 composition.…”
Section: Discussionsupporting
confidence: 91%
“…It was reported previously in pomegranate juices; the diglucoside AC was more stable than the monoglucosides. 8 This was parallel with present study and Dionex; 9 Cy3, 5 and Pg3, 5 compositions are higher than Cy3 and Pg3. However, this was contrary to Miguel et al 6 in which there was a high decrease of Cy3, 5 than Cy3 composition.…”
Section: Discussionsupporting
confidence: 91%
“…The 1.0 M sugar-blueberry juice solutions, which showed the lowest color intensity, were selected for further examination of the effect on storage time. Sealed test tubes of 1.0 M sugar added blueberry juice were stored at 30°C during 10 days, and the absorbance changes were measured at 514 nm every 24 h (15). …”
Section: Methodsmentioning
confidence: 99%
“…Sealed test tubes were stored at 30°C for 10 days and changes in absorbance measured every 24 h at 514 nm. Color retention (%) was calculated as the quotient of the absorbance value after storage divided by the initial reading (15). …”
Section: Methodsmentioning
confidence: 99%
“…Conventionally, extraction of anthocyanins and phenolics with desirable yields has been carried out with solvents such as methanol, ethanol, and ethanol in hydrochloric acid medium (Pedro et al, 2015). For example, although anthocyanins are soluble in water, researchers observed that ethanol and methanol PSP extracts had approximately 3-4 times higher values of anthocyanins compared to water extracts from (Bridgers et al, 2010).…”
mentioning
confidence: 99%